Potential Biomarkers Indicating Resistance or Resilience in Experimental Peri-Implant Mucositis: A Systematic Review and Meta-Analysis - Huamán-Mendoza, Aldrin André; do Amaral, Guilherme Castro Lima Silva; Vilela, Nathalia; Chuquimez-Ventura, Casimira Valeria; Rovai, Emanuel Silva [UNESP]; Romito, Giuseppe Alexandre; Pannuti, Claudio Mendes; Villar, Cristina Cunha; Holzhausen, Marinella (Wiley, 2025)
Objectives: To identify changes in immunological, microbiological, and histological biomarkers that may indicate resistance during the induction phase and resilience during the resolution phase of experimental peri-implant mucositis (PiM). Materials and Methods: The search was performed in MEDLINE, EMBASE, Web of Science, SCOPUS, Cochrane Library, and LILACS databases. Prospective interventional studies assessing biomarkers during experimental PiM were included. The risk of bias was assessed using the Risk Of Bias In Non-Randomized Studies of Interventions (ROBINS-I) tool. Meta-analyses were conducted using random-effects models. The GRADE approach was used to determine the certainty of evidence. Results: Eleven out of 6008 studies were included. Clinical parameters (mPI and mGI) effectively characterized the experimental PiM model. Due to methodological variability and conflicting results, a definitive interpretation of microbiological and histological biomarkers was not possible. The meta-analysis revealed that IL-1β and the volume of peri-implant crevicular fluid (PICF) indicated non-resistance during the induction phase. In contrast, TNF-α, IL-6, IL-8, IL-17, MMP-8, and IFN-γ remained stable. Regarding the resolution phase, IL-1β returned to baseline levels (SMD: 1.13; 95% CI: −0.81, 3.06), and the volume of PICF (MD: 0.08; 95% CI: 0.03, 0.13) remained significantly elevated compared to day 0. However, TNF-α, IL-6, IL-8, IL-17, MMP-8, and IFN-γ did not significantly differ from baseline levels. Conclusions: Moderate to very low evidence suggested that the biomarkers IL-1β and the volume of PICF indicated a lack of resistance while suggesting resilience and non-resilience, respectively. The biomarkers TNF-α, IL-6, IL-8, IL-17, MMP-8, and IFN-γ demonstrated resistance and resilience.
Keywords: biomarkers; dental implants; evidence-based dentistry; inflammation; meta-analysis; systematic review